2016
DOI: 10.1016/j.drugalcdep.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Methadone maintenance therapy and viral suppression among HIV-infected opioid users: The impacts of crack and injection cocaine use

Abstract: Background Methadone maintenance therapy (MMT) is associated with improved HIV treatment outcomes among people who use drugs (PWUD). The extent to which these benefits are sustained in the context of ongoing cocaine use is unclear. We assessed differential impacts of MMT on HIV viral load (VL) suppression in relation to discrete patterns of cocaine use. Methods Data was drawn from ACCESS, a prospective cohort of HIV-positive PWUD in Vancouver, Canada. Generalized linear mixed-effects were used to model the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…However as in the study reported here, there was a positive correlation between continuing addiction treatment and undetectable VL (23). A second study assessed the relationship between undetectable VL (<50 copies per mL) and cocaine use among 304 HIV-infected, methadone maintained opioid/cocaine users in Vancouver, Canada and found that undetectable VL's ranged from 58-70% depending on whether the patient was injecting cocaine less than daily or using crack once or more a day (24). A third study recruited 295 HIV-infected opioid addicted individuals, 176 on ART and 119 not on ART, and started them on sublingual buprenorphine/naloxone (bup/nal).…”
Section: Discussionmentioning
confidence: 54%
“…However as in the study reported here, there was a positive correlation between continuing addiction treatment and undetectable VL (23). A second study assessed the relationship between undetectable VL (<50 copies per mL) and cocaine use among 304 HIV-infected, methadone maintained opioid/cocaine users in Vancouver, Canada and found that undetectable VL's ranged from 58-70% depending on whether the patient was injecting cocaine less than daily or using crack once or more a day (24). A third study recruited 295 HIV-infected opioid addicted individuals, 176 on ART and 119 not on ART, and started them on sublingual buprenorphine/naloxone (bup/nal).…”
Section: Discussionmentioning
confidence: 54%
“…Opioid-dependent individuals stabilized on MMT are highly diverse and beyond the benefit of HIV TasP efforts. In the broader literature, several factors have been associated with viral suppression (Aibibula et al, 2018; Arthur et al, 2015; Bowen et al, 2017; Crepaz, Tang, Marks, & Hall, 2017; Ferrand et al, 2016; Socías et al, 2016). Despite substantial research in this area, prior studies have not explored theoretically informed correlates among HIV-infected opioid-dependent patients within drug treatment settings.…”
Section: Introductionmentioning
confidence: 99%
“…All 5 studies that analyzed the effect of MOUD on HIV viral suppression reported a significant relationship ( Table 1 ) [ 19 , 22–25 ]. Reddon et al [ 22 ], Roux et al [ 23 ], and Socías et al [ 24 ] reported significant effects of methadone treatment on viral suppression at 6 months. Both studies by Springer et al [ 19 , 25 ] reported viral suppression to be HIV-1 ribonucleic acid (RNA) <50 copies/mL with statistically significant improvement with BPN or XR-NTX.…”
Section: Results and Findingsmentioning
confidence: 99%